ANALISIS PENGARUH PAJAK REKLAME DAN PAJAK HIBURAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA JAMBI PERIODE 2019-2024 - Bella Savitri Hulu; Haviz Taufik; Aditya Pradana (STKIP Subang, 2026)
This study aims to analyze the development, contribution level, and effectiveness of Advertising Tax and Entertainment Tax on Regional Original Income (PAD) in Jambi City during the 2019–2024 period. The research method used is a quantitative method with a descriptive and explanatory verification approach. The sample was determined using thepurposive samplingwith a focus on the realization of targets and revenues from Advertising Tax, Entertainment Tax, and the total PAD of Jambi City. Data analysis tools used include contribution ratio analysis, effectiveness ratio analysis, and descriptive statistical analysis with the help of SPSS software. The results of the study indicate that the contribution of Advertising Tax and Entertainment Tax to the Regional Original Income (PAD) of Jambi City during the 2019–2024 period is categorized as